Running training combined with blood flow restriction increases cardiopulmonary function and muscle strength in endurance athletes - Chen, Y.-T.; Hsieh, Y.-Y.; Ho, J.-Y.; Lin, T.-Y.; Lin, J.-C. (The Journal of Strength and Conditioning Research, 2022)
We investigated the effects of 8 weeks (3 d/wk) of running training (RT) combined with blood flow restriction (RT-BFR) on cardiopulmonary function and muscle strength in endurance athletes. Twenty endurance-trained male athletes (19-25 years; 177.6 ± 2.4 cm; 69.0 ± 2.2 kg) were pair matched and randomly assigned to RT-BFR and RT groups. The RT-BFR group performed running sessions (50% heart rate reserve; 3-minute × 5 sets; 1-minute rest interval) with pressure cuffs (1.3 × resting systolic blood pressure), whereas the RT group performed the same running sessions without pressure cuffs. Vo2max, muscle mass, isokinetic muscle strength, and hormones were assessed at pre-, mid- and posttraining. Compared with the RT group, the RT-BFR group exhibited a significantly greater increase in Vo2max (5.1 vs. -1.1%) and isokinetic knee extensor strength (16.5 vs. -5.9%). In addition, RT-BFR group presented higher leg muscle mass (10.3 vs. 9.7 kg) than that of RT group after 8 weeks of training. Furthermore, testosterone to cortisol (T:C) ratio at 24 hours after training session at pre-, mid-, and posttraining were maintained in the RT-BFR group, whereas significant decreases of T:C ratio at 24 hours after training session were observed in the RT group. These results suggested that RT combined with BFR may be a practical training strategy for promoting cardiopulmonary function and muscle strength in endurance runners.